PROSES TRANSIVITAS DALAM PERIKLANAN SIARAN LANGSUNG TIKTOK SHOP : SUATU KAJIAN LINGUISTIK SISTEMIK FUNGSIONAL - Fitriyani, Andi Nurul; Mahmudah, Mahmudah; Jahrir, Andi Sahtiani (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
The aim of this research is to describe the forms of transitivity processes using qualitative methods with descriptive explanations. The data source in this research is primary data sourced from online traders' buying and selling advertisements on the Tiktok shop application, especially clothing, beauty equipment and viral food which are advertised directly. The results of this research found that the transitivity process that dominates is the material process which shows actions marked by verbs in the form of promotions or offers, how to use or recommendations related to beauty products, food and clothing. This aims to attract the attention of TikTok application users, which implies that TikTok users will be interested in buying the advertised product.